Pengaruh Buku Suplemen Digital Terintegrasi Mitigasi Bencana terhadap Keterampilan Kolaborasi Peserta Didik - Parawansa, Fahira Satma; Fadilah, Muhyiatul (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
Collaboration skills are a process carried out in groups to discuss differences through listening, giving suggestions, listening to discussions and respecting differences of opinion. Student collaboration skills can be dangerous in the learning process, one of which is by utilizing digital-based learning media. Digital supplement books are complementary books to printed books which contain reading text, images, video, audio and other information that can be read on smartphones, laptops and other portable devices. The purpose of this study was to determine the effect of disaster-integrated digital supplement books on students' training skills. This research was conducted using the Quasi Experiment research method (pseudo-experiment). The data collection technique for this research was an observation sheet filled in by two observers at each meeting and a questionnaire filled in individually by students. The average observation sheet for the collaboration skills of students in the experimental class was higher than that of the control class, namely 71 for the experimental class and 59 for the control class. At the level of student collaboration skills, the average value of the experimental class was 91% greater than that of the control class, which was 79%. From this study it can be interpreted that the integrated digital supplement book on the impact of disasters has an effect on the skills of the trainees.